The Role of Anida's Tari Pattennung as a Medium for Developing Multiple Intelligences in Elementary School Children at UPT SDN 11 Pangsid Sidenreng Rappang - Miftahul Jannah; Imron Burhan (Cita konsultindo, 2025)
This study aims to examine the role of Anida's Tari Pattennung as a medium for developing various aspects of intelligence in elementary school children at SD Negeri 11 Pangsid. Using a descriptive qualitative approach, this research explores the impact of Tari Pattennung on the development of kinesthetic, musical, interpersonal, intrapersonal intelligences, as well as cultural awareness among students. The findings show that through Tari Pattennung, students not only develop physical skills and motor coordination (kinesthetic) but also enhance their sensitivity to traditional music (musical), improve their ability to collaborate in groups (interpersonal), and build self-confidence and emotional expression (intrapersonal). Furthermore, students demonstrate a greater interest in the history and cultural significance of the Bugis culture, particularly in relation to the fabric weaving process, which is an integral part of the dance. This activity helps to foster a strong cultural awareness in children, introducing them to the richness of local culture that needs to be appreciated and preserved. This study recommends that traditional dance arts, such as Tari Pattennung, be more widely integrated into elementary education to support the development of multiple intelligences and the preservation of cultural heritage among the younger generation.